Pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) Dalam Persiapan Persalinan - Sukarsih, Rachmawati Ika (Sinar : Jurnal Kebidanan, 2024)
Objective: Abstract Breast milk (mother's milk) is the only natural food for babies.  Preparation for childbirth is everything that is understood and prepared in terms of welcoming the birth of a child by pregnant women. Preparation for childbirth is an important part of the delivery process, aimed at improving optimal health before childbirth. Based on 2018 Riskesdas data regarding ownership of KIA books in Indonesia, there are still 24.9% of pregnant women who do not have KIA books. This research aims to determine the use of Maternal and Child Health (KIA) books in preparation for childbirth at the Jagir Surabaya Community Health Center. Methods: This research is a quantitative research with a descriptive design. In this research, the sample collection technique used purposive sampling with a population of 45 respondents and a sample of 40 respondents. The data collection technique used in this research is primary data in the form of a questionnaire. Results: The results of the research showed that 40 pregnant women (100%) carried the MCH book during the examination well, 21 pregnant women (52.5%) read the MCH book well, and 30  pregnant women applied the contents of the MCH book well (75%). Conclusion: The use of the MCH book can be assessed from three aspects, including bringing the MCH book when carrying out examinations, reading the contents of the MCH book, and applying the messages contained in the MCH book, one of which is regarding childbirth preparation.